X‐ray computed tomography to predict soil N2O production via bacterial denitrification and N2O emission in contrasting bioenergy cropping systems. Issue 11 (16th September 2018) - Kravchenko, Alexandra N.; Guber, Andrey K.; Quigley, Michelle Y.; Koestel, John; Gandhi, Hasand; Ostrom, Nathaniel E.
Abstract: While renewable biofuels can reduce negative effects of fossil fuel energy consumption, the magnitude of their benefits depends on the magnitude of N2 O emissions. High variability of N2 O emissions overpowers efforts to curb uncertainties in estimating N2 O fluxes from biofuel systems. In this study, we explored (a) N2 O production via bacterial denitrification and (b) N2 O emissions from soils under several contrasting bioenergy cropping systems, with specific focus on explaining N2 O variations by accounting for soil pore characteristics. Intact soil samples were collected after 9 years of implementing five biofuel systems: continuous corn with and without winter cover crop, monoculture switchgrass, poplars, and early‐successional vegetation. After incubation, N2 O emissions were measured and bacterial denitrification was determined based on the site‐preference method. Soil pore characteristics were quantified using X‐ray computed microtomography. Three bioenergy systems with low plant diversity, that is, corn and switchgrass systems, had low porosities, low organic carbon contents, and large volumes of poorly aerated soil. In these systems, greater volumes of poorly aerated soil were associated with greater bacterial denitrification, which in turn was associated with greater N2 O emissions ( R 2 = 0.52, p < 0.05). However, the two systems with high plant diversity, that is, poplars and early‐successional vegetation, over the 9 years of implementation had developed higher porosities and organic carbon contents. In these systems, volumes of poorly aerated soil were positively associated with N2 O emissions without a concomitant increase in bacterial denitrification. Our results suggest that changes in soil pore architecture generated by long‐term implementation of contrasting bioenergy systems may affect the pathways of N2 O production, thus, change associations between N2 O emissions and other soil properties. Plant diversity appears as one of the factors determining which microscale soil characteristics will influence the amounts of N2 O emitted into the atmosphere and, thus, which can be used as effective empirical predictors. Abstract : Long‐term implementation of bioenergy systems with contrasting plant diversity influences microscale pore architecture, which then affects predictors of N2 O production and emission.